Retroperitoneal lymphadenopathy secondary to joint replacement wear and debris, a case report - C. Calo; H. Preston; A. Clements (Elsevier, 2018)
We present a case of a 63-year-old female who initially presented with complaints of vulvar swelling and was subsequently found to have isolated retroperitoneal lymphadenopathy on imaging. Biopsy was performed and was indicative of weakly polarizable material that raised the consideration of joint prosthesis wear debris. Due to the patient's concern for an underlying malignancy of gynecologic origin, a laparoscopic lymphadenectomy was ultimately performed and final pathology was consistent with reactive changes due to joint wear and debris from the patient's bilateral total knee arthroplasties placed approximately 16 years prior. While this is a rare presentation, it is important to consider this in the differential of retroperitoneal lymphadenopathy as these patients are often referred to a gynecologic oncologist for further workup.